The darker perspective behind skin lightening practices and its effect on mental Health - Nadia Farooq; Azra Shaheen; Naseem Amin Dhedi; Tayyaba Iqbal (Journal of University Medical & Dental College, 2024)
ABSTRACT BACKGROUND AND OBJECTIVE: In Pakistan, individuals seem to have a strong preference for a light skin tone due to it being one of the criteria that defines “beauty” universally. There is a plethora of research that has investigated the implications of darker skin color and the role media and culture has played in it. The current study aims to find out the reasons people seek fairer skin tones as well as the prevalence of stress, anxiety, and depression among them in Pakistan. METHODOLOGY: The study was conducted over a period of 6 months in the dermatology OPD of Fatima Hospital Baqai Medical University, Karachi where 250 individuals participated (196 = females, 54 = males) by non-probability purposive sampling. Just over 60% (172 individuals) of the sample size indicated that they fell in the dark skin color category. The results suggest that anxiety, depression, and stress have a significant association with skin tone (p-value< 0.05). RESULTS: The reasons for adopting skin-lightening treatments were diverse;90(36%) of participants reported that they are using the treatment for fairness because of their own will,87( 35) indicated media, and 73(29) selected relatives/friends/husbands. They were also asked to fill DASS-21 scale to determine the levels of stress, anxiety, and depression that come with the pressure of seeking fair treatments. CONCLUSION: This study highlighted that skin tone is an important determinant of mental health and impacts the lives of women and men individuals with darker skin face more anxiety, depression, and stress due to sociocultural pressure.